Analisis Hubungan Faktor Lingkungan Dengan Keberadaan Tikus Di Asrama Pelaut Tanjung Priok Jakarta Utara Tahun 2025 - Atang Saputra; Rahma Aristara Barakati; Syamsu Alam; Syarifuddin (CV. Multi Kreasi Media, 2026)
Background: Rats are carriers of diseases such as Leptospirosis and Hantavirus. Furthermore, rats are known as parasitic rodents of humans. The dynamics of rat life are influenced by abiotic environmental factors and sanitation facilities, such as temperature, humidity, and waste containers. This study aims to analyze the relationship between temperature, humidity, and waste containers with the presence of rats at the Tanjung Priok Seafarers' Dormitory, North Jakarta. Methods: This study used a cross-sectional approach. Data were statistically analyzed to determine the relationship between environmental factors and the presence of rats at the location. The study ran from January to June 2025. Results: Of the 50 traps set, the success rate was 20%. The analysis showed that temperature was significantly associated with rat presence (p = 0.013), while humidity (p = 1.000) and waste containers (p = 0.065) did not show a significant relationship. Conclusion: Rat density at the Tanjung Priok Seafarers' Dormitory is relatively high. There is a statistical relationship between temperature and the presence of rats, but there is no significant relationship between humidity or trash containers and the presence of rats.